2011
DOI: 10.1097/won.0b013e31820ad0fd
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Pressure Ulcer Risk During Hospital Procedures

Abstract: A 300-bed acute care community hospital used a 2-day "Rapid Process Improvement Workshop" to identify factors contributing to facility-acquired pressure ulcers (PU). The Rapid Process Improvement Workshop included key stakeholders from all procedural areas providing inpatient services and used standard components of rapid process improvement: data analysis, process flow charting, factor identification, and action plan development.On day 1, the discovery process revealed increased PU risk related to prolonged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…; Haugen et al. ). In general, however, these reports suggest that POPs have adverse effects on reproductive health outcomes.…”
Section: Teratological Environmental Factors (Endocrine Disruptors) Amentioning
confidence: 98%
See 1 more Smart Citation
“…; Haugen et al. ). In general, however, these reports suggest that POPs have adverse effects on reproductive health outcomes.…”
Section: Teratological Environmental Factors (Endocrine Disruptors) Amentioning
confidence: 98%
“…Because of the stability and bioaccumulation of these compounds in the environment, human populations are simultaneously exposed to a variety of those contaminants through the consumption of food. Several POPs have been shown to have toxic effects on reproductive and endocrine functions in humans (Govarts et al 2012) and a number of human epidemiological studies have demonstrated the adverse effects of POPs exposure on markers of reproduction, including semen quality (sperm concentration, motility, and morphology) (Guo et al 2000;Richthoff et al 2003;Toft and Guillette 2005;Meeker et al 2010), spermatic DNA integrity (Bonde et al 2008;McAuliffe et al 2012), and circulating reproductive hormone levels (Richthoff et al 2003), though some studies found only marginal effects (Toft et al 2006;Haugen et al 2011). In general, however, these reports suggest that POPs have adverse effects on reproductive health outcomes.…”
Section: Teratological Environmental Factors (Endocrine Disruptors) Amentioning
confidence: 99%
“…Researchers reviewed 17 medical records of patients who developed HAPIs and found that 13 of the 17 patients had undergone multiple procedural interventions during their hospital course, including cardiac catheterization, radiological procedures, and surgery. 25 Perioperative personnel should consider a patient's time spent in the ED and on interventional units (eg, interventional radiology, endoscopy), and his or her multiple transfers during transport before entering the OR when determining pressure injury risk. 22,25 The prevention landscape has evolved in perioperative areas during the past five years.…”
Section: Risk Factorsmentioning
confidence: 99%
“…25 Perioperative personnel should consider a patient's time spent in the ED and on interventional units (eg, interventional radiology, endoscopy), and his or her multiple transfers during transport before entering the OR when determining pressure injury risk. 22,25 The prevention landscape has evolved in perioperative areas during the past five years. In 2014, the NPUAP identified the OR as a high-risk environment and devoted a section in its clinical practice guideline to perioperative pressure injury prevention.…”
Section: Risk Factorsmentioning
confidence: 99%
“…A wide range of quality improvement methods has been used to support the implementation of interventions and processes in healthcare, including the Lean/Six Sigma Rapid Process Improvement Workshop (RPIW) [28,29]. Multiple healthcare institutions have improved the quality of care through the utilization of variations of RPIWs [30,31]. RPIWs can be effective for implementing evidence-based practices in behavioral health care [32], and they have the advantages of being customer/patient-centered and balancing the role of both measurement/data and people in effectively implementing an EBP [28].…”
Section: Implementation Strategiesmentioning
confidence: 99%